Incongruence between confirmed and suspected clinical cases of Japanese encephalitis virus infection - Li, Wei; Feng, Yuliang; Zhong, Hongrong; Jiang, Mingfeng; Zhang, Jiake; Lin, Shihua; Chen, Na; He, Shusen; Zhang, Kai; Fu, Shihong; Wang, Huanyu; Liang, Guodong (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Japanese encephalitis is a notifiable infectious disease in China. Information on every case of JE is reported to the superior health administration department. However, reported cases include both laboratory-confirmed and clinically diagnosed cases. Methods: All acute-phase serum and/or CSF samples of the reported JE cases were screened for IgM to JEV using the ELISA, and the detection of the viral genes of JEV and 9 other pathogens, using RT- PCR was attempted. Epidemiological analyses of JE and non-JE cases based on sex, age, onset time, and geographical distribution were also performed. Results: From 2012 to 2022, 1558 JE cases were reported in the Sichuan province. The results of serological (JEV-specific IgM) and genetic testing for JEV showed that 81% (1262/1558) of the reported cases were confirmed as JEV infection cases . Among the 296 cases of non-JEV infection, 6 viruses were detected in the CSF in 62 cases, including EV and EBV, constituting 21% (62/296) of all non-JE cases. Additionally, there were five cases involving mixed infections. The remaining 234 cases were classified as unknown viral encephalitis cases. Our analysis indicated that those aged 0–15 y were the majority of the patients among the 1558 reported JE cases. However, the incidence of laboratory-confirmed JE cases in the >40 y age group has increased in recent years. The temporal distribution of laboratory-confirmed cases of JE revealed that the majority of cases occurred from July to September each year, with the highest incidence in August. Conclusion: The results of this study indicate that there is a certain discrepancy between clinically diagnosed and laboratory-confirmed cases of JE. Each reported case should be based on laboratory detection results, which is of great importance in improving the accuracy of case diagnosis and reducing misreporting. Our results are not only important for addressing JE endemic to the Sichuan province, but also provide a valuable reference for the laboratory detection of various notifiable infectious diseases in China and other regions outside China.